Making the Grade (But Not Disclosing It): How Withholding Grades Affects Student Behavior and Employment - Floyd, Eric; Tomar, Sorabh; Lee, Daniel J. (Management Science, 2024)
We study the effects of grade nondisclosure (GND) policies implemented within master of business administration (MBA) programs at highly ranked business schools. GND precludes students from disclosing their grades and grade point averages (GPAs) to employers. In the labor market, we find that GND weakens the positive relation between GPA and employer desirability. During the MBA program, we find that GND reduces students’ academic effort for a given course by approximately 4.9% relative to comparable students not subject to the policy. Consistent with our model, in which abilities are potentially correlated and students can substitute effort toward other activities in order to signal GPA-focused abilities, students participate in more extracurricular activities and enroll in more difficult courses under GND. Finally, we show that students’ tenure with their first employers after graduation decreases under GND. This paper was accepted by Suraj Srinivasan, accounting. Supplemental Material: The online appendix and data are available at https://doi.org/10.1287/mnsc.2023.4816 .